A codex of care: Assessing the Liverpool Hospital Admission and Discharge Protocol for Homeless People. (June 2015) - Whiteford, Martin; Simpson, Glenn
There has recently been an upsurge of interest in the relationship between homelessness and hospital discharge policies and processes in England. In this paper, we investigate the significance of these developments by assessing the Liverpool Hospital Admission and Discharge Protocol for Homeless People. Drawing on in-depth qualitative interviews with hospital-based clinicians and community-based health and social care practitioners, we identify four central features of the Liverpool protocol: (1) local prioritisation, (2) good systems of communication, (3) partnership working and (4) access to appropriate post-discharge care and support. Overall, we contribute to the literature of care coordination by filling a gap in the knowledge base in relation to the multiple and complex needs of homeless people, while delivering important insights into the delivery of integrated care.